Reviewing the correlation potential of Spectral Gamma Ray: a case study in Ordovician glacial environments in the Murzuq basin, SW Libya. (April 2022) - Bataller, F.J.; McDougall, N.D.; Moscariello, A.
Abstract: The deposits of the Late Ordovician glaciation have been the focus of several studies in recent years reflecting significant hydrocarbon reservoir potential in different areas of the world, most notably in Libya and Algeria but also in Saudi Arabia and Bolivia. The study area for this paper is located within the Murzuq Basin of SW Libya. This study aims to evaluate the potential of Spectral Gamma Ray, integrated with other datasets (geochemical data, core descriptions and Micro-resistivity Images) to enhance correlation in glacial reservoirs where biostratigraphy cannot be applied and conventional logs lack resolution or consistency. The methodology chosen correlates the SGR logs and elemental ratios in wells with geochemical and sedimentological data to understand possible relationships between Th, U, K and depositional environments. Subsequently, this tool is used to analyse wells for which no detailed sedimentological data is available to understand the spatial configuration of depositional environments, correlation and thus, reservoir potential across the study area. The study demonstrates how the use of the SGR ratios can be useful as a correlation tool, how Th/U varies with distance from the sediment source area; but also highlights that whilst SGR ratios are not able to consistently discriminate between individual facies associations, given the large standard deviations, they are nonetheless very useful as general predictors of broad depositional. Additionally, a review of possible sources for the Th and U is provided together with some conclusions aimed at improving the understanding of the architecture of the glacial sediments. Highlights: Spectral GR, is a good, complementary tool to improve correlation in glaciogenic reservoirs. The Th/U ratio in glacial sediments show weak correlation with specific Facies Associations. Th/U ratio, is useful to identify surfaces that help improve correlations in glacial sediments.